Vegetable Production and Marketing in Africa: Socio-Economic Research 2011
DOI: 10.1079/9781845936495.0085
|View full text |Cite
|
Sign up to set email alerts
|

Food production standards and farm worker welfare in Kenya.

Abstract: This chapter focuses on the effect of private food production standards on the welfare of farm workers in Kenya. The chapter is divided into several sections. The section, Conceptual Framework and Methodology, describes the application of the Sen?s functionings approach in the context of production standards in horticulture. The section Survey Design and Data describes the design of the survey and the process of data collection. An overview of the collected data is given in section Empirical Models and Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Blunch and Castro (2005) show that International Organization for Standardization (ISO) certification increases workers’ training in textile, garment and food industries in five developing countries. Ehlert et al (2011) find that workers at farms in Kenya that are certified by GlobalGAP, which is the most important private standard in African horticulture, are better trained, but find no significant difference in workers’ incomes or health.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Blunch and Castro (2005) show that International Organization for Standardization (ISO) certification increases workers’ training in textile, garment and food industries in five developing countries. Ehlert et al (2011) find that workers at farms in Kenya that are certified by GlobalGAP, which is the most important private standard in African horticulture, are better trained, but find no significant difference in workers’ incomes or health.…”
Section: Introductionmentioning
confidence: 87%
“… In Kenya, the number and intensity of training sessions is found to be higher at GlobalGAP farms (Ehlert et al, 2011), and training of farmers and workers is found to account for an important part of the costs of GlobalGAP certification (Graffham et al, 2007). Our interviews with Senegalese companies revealed that training of workers (with respect to the application of chemicals, record‐keeping, safety and hygiene) is costly, especially given low literacy levels and the scarcity of qualified labour to organise training. …”
mentioning
confidence: 99%
“…GlobalGAP certification is about good agricultural practices and it allows suppliers of horticultural products (farmers) to undergo quality training where new methods of planting, harvesting and so on are taught to improve agricultural productivity (Ehlert et al, 2011). In this way, good agricultural practices are applied throughout the food production process (ITC, 2011).…”
Section: The Importance Of Globalgap (Good Agricultural Practices)mentioning
confidence: 99%
“…Adequate knowledge of global horticulture supply chains and stringent adherence to requirements have a significant impact on export performance. An awareness of good agricultural practices (GlobalGAP) (Ehlert et al, 2011) is one of the several standards to comply with. According to the findings, suppliers are ignorant of these standards and have not been complying with export regulations.…”
Section: Stakeholders' Incompetencementioning
confidence: 99%
See 1 more Smart Citation